Effects of psyching-up on sprint performance - Hammoudi-Nassib, S.; Nassib, S.; Chtara, M.; Briki, W.; Chaouachi, A.; Tod, D.; Chamari, K. (The Journal of Strength and Conditioning Research, 2017)
The present research aimed at examining whether the psyching up (PU) strategies improve performance in 30-m sprinting. Sixteen male sprinters (age, 20.6 ± 1.3 years; body mass, 77.5 ± 7.1 kg; height, 180.8 ± 5.6 cm) participated in this study. Before each experimental session, the Hooper index was used to monitor the subject`s feeling for the quality of sleep of the previous night, perceived quantity of stress, delayed onset muscle soreness, and fatigue. After completing general and specific warm-up, participants had to rate their degree of self-confidence. Then, they were asked to follow 1 of these 4 conditions: Imagery (experimental PU condition), Preparatory arousal (experimental PU condition), Attention placebo (control condition), and Distraction (control condition) during the final 30 seconds of the rest period right before performing a 30-m sprint. Participants separately and randomly performed all conditions. Results showed that although the imagery and preparatory arousal strategies contributed to increase the performance in the short-distance sprints (from 0 to 10 m), the imagery strategy contributed to increase the performance in the 30-m sprints. These findings support the general view that the PU strategies could improve athletic performance.